The microstructure of China's government bond market - Jennie Bai; Michael Fleming; Casidhe Horan (Federal Reserve Bank of New York, 2013)
Although China now has one of the largest government bond markets in the world, the market has received relatively little attention and analysis. We describe the history and structure of the market and assess its functioning. We find that trading in individual bonds was historically sparse but has increased markedly in recent years. We find also that certain announcements of macroeconomic news, such as China's producer price index (PPI) and manufacturing purchasing managers' index (PMI), have significant effects on yields, even when such yields are measured at a daily level. Despite the increased activity in the market, we are able to reject the null hypothesis of market efficiency under two different tests for four of the most actively traded bonds.
Keywords: G12; G14; E43; 330; trading activity; market efficiency; announcements; interest rates